Propriété, biens publics mondiaux, bien(s) commun(s) : Une lecture des concepts économiques - Jérôme Ballet (Développement Durable et Territoires)
Property, Global Public Goods, Common Good(s) : A Lecture. The concept of global public good emerged these last years. It proposes, in an ambiguous way, to go beyond the usual concept of public good. Then, added to usual questions on efficiency, the debate on fairness becomes a stake. Confrontation with analysis on property rights command attention, Furthermore, confrontation with the concept of common good, also a developing concept, highlight stake around fairness.